Beyond the Bottle: A Practical Guide to Recognizing Problem Drinking, Identifying Liver Fibrosis and Knowing When to Refer - Elyssa Del Valle (Journal of Mental Health Disorders, 2026)
Alcohol use and maladaptive coping behaviors, including excessive consumption of ultra-processed foods, are increasingly recognized as important contributors to both psychiatric illness and chronic liver disease. Many patients self-treat anxiety, insomnia, trauma, chronic pain, or mood disorders with alcohol without recognizing hazardous drinking patterns. In the setting of the global rise in Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD), even modest alcohol intake may accelerate progression to Alcohol-Associated Liver Disease (ALD), advanced fibrosis, cirrhosis, and hepatocellular carcinoma. These risks are particularly concerning given the marked rise in alcohol use disorder and alcohol-related liver disease among women. Because advanced fibrosis is often clinically silent, subtle laboratory abnormalities, incidental imaging findings, or mild cognitive and functional decline may be the earliest indicators of liver injury. Mental health clinicians, who often follow patients longitudinally, are uniquely positioned to identify these red flags and facilitate timely referral for further evaluation. This practical commentary highlights the intersection of psychiatric illness, alcohol use, metabolic dysfunction, and chronic liver disease while providing clinicians with key clinical clues that warrant referral to primary care, gastroenterology, or hepatology, where early intervention may prevent progression and even allow regression of liver fibrosis.